USING SONGS TO TEACH GRAMMAR EFFECTIVELY IN EFL CLASSROOMS - Dildora , Uljaboyeva Jaloldin qizi (Educational Research in Universal Sciences, 2023)
The purpose of this study was to identify the importance of song based activities in teaching grammar structures to students at school 34 in Mingbulak district Namangan region. To gather data online survey was held among EFL teachers. Two participating groups were selected deliberately, 7A as a control and 7B as an experimental. Song based activities were given 7B students while pre and post tests which measured the students’ grammar competence were taken from both groups. The test results were scored and compared.